Time is of the Essence: Climate Adaptation Induced by Existing Institutions - Antonio M. Bento; Noah Miller; Mehreen Mookerjee; Edson R. Severnini (Institute of Labor Economics (IZA), 2021)
In the absence of first-best climate policy, we demonstrate that existing government institutions and policy established for reasons unrelated to climate change may induce climate adaptation. We examine the impact of temperature on ambient ozone concentration in the United States from 1980-2013, and the role of institution-induced adaptation. Ozone is formed under warm temperatures, and regulated by the Clean Air Act institution. Adaptation in counties out of attainment with air quality standards is 107 percent larger than under attainment, implying substantial institution-induced adaptation. Furthermore, local beliefs about climate change appear to reinforce adaptive behavior, suggesting a nontrivial role in second-best climate policy.
Keywords: Q53; Q54; Q58; H23; K32; P48; D02; 330; climate change; government institutions and policy; Clean Air Act; institution-induced adaptation; ambient ozone concentration; climate change beliefs